Using Attainment of the Designated Aquatic Life Use to Determine Adverse Environmental Impact - Greg Seegert (The Scientific World Journal)
Section 316(b) of the Clean Water Act requires that cooling-water intake structures (CWIS) use Best Technology Available (BTA) to minimize adverse environmental impacts (AEI). The U.S. EPA has not defined AEI, and there is no clear consensus regarding its definition. Nonetheless, operational definitions are necessary to evaluate design alternatives and to measure the success of mitigative measures. Rather than having to develop measures of aquatic health that are highly site-specific, controversial, and often unlikely to elicit agreement from all sides of the environmental “fence”, it may be more productive to use existing ecological assessment tools. Aquatic Life Uses (ALU) already provide a regulatory framework to assess the quality (health) of the aquatic community in various habitats (e.g., warmwater habitat, exceptional warmwater habitat). Attainment of the ALU indicates that further point source controls are unnecessary, whereas nonattainment indicates that those pollutants or stressors causing the nonattainment must be reduced. A similar approach for existing water intakes is recommended. That is, attainment of the designated ALU will be taken as an indication that there is no AEI. Although attainment of the ALU may not be a foolproof indicator of a lack of AEI, this approach seems more reasonable that using scarce monetary resources to fix problems that likely do not exist, or having both regulators and the regulated community expend their resources debating whether various observed biological responses do or do not constitute AEI.